Employing resilience in the United States Forest Service. (March 2016) - Bone, Christopher; Moseley, Cassandra; Vinyeta, Kirsten; Bixler, R. Patrick
Highlights: We evaluate how the USFS engages in engineering, ecological, social and social-ecological resilience. A content analysis revealed that the USFS employs different resilience concepts. Resilience is most-often employed in discourse surrounding the need to adapt to wildfire. Ambiguity with resilience can leave policy implementation open to individual interpretation. Abstract: The concept of resilience has permeated the discourse of many land use and environmental agencies in an attempt to articulate how to develop and implement policies concerned with the social and ecological dimensions of natural disturbances. Several distinct definitions of resilience exist, each with its own concepts, focus and contexts related to land use policy and management. This often makes understanding the inherent objectives of policies and related principles challenging. The United States Forest Service (USFS) is one example where ambiguity and uncertainty surrounding the use of resilience permeates the content of documents in various areas of the agency. The objective of this paper is to investigate how the USFS employs the term resilience as a means to communicate strategies for managing forest lands. We perform a content analysis of 121 USFS documents including budgetary justification reports, research findings (i.e., journal articles, book chapters and technical reports), public releases, and newsletters to analyze both the rise and specific use of the term resilience in the USFS. Our analysis, which is guided by definitions of resilience in the social-ecological systems literature, reveals that the ambiguity surrounding the use of resilience in the academic literature is reflected in the content of USFS documents. However, we also find that often criticized versions of resilience (namely engineering resilience) are minimally employed by the USFS, and instead the agency focuses on the notion of ecological resilience in which natural disturbances are seen as an important component of the landscape. In some cases, the USFS employs notions of social-ecological resilience, however, the extent to which specific components of social-ecological resilience are integrated into management strategies appears minimal. The findings from this study suggest that clarity regarding the type and function of resilience needs to improve in USFS documents, and that the agency should evaluate the existing question in the SES literature of resilience of what to what?